Foreign language teaching anxiety of in-service teachers in Serbia – the importance of recognising and alleviating it - Marinković, Ivana (Studies in Teaching and Education, 2025)
Foreign language teaching anxiety (FLTA) is a characteristic of non-native FL teachers, which prevents them from using language-intensive activities and spontaneous communication in the classroom, thus reducing the effectiveness of teaching. It increases foreign language learning anxiety (FLLA), which is considered to have the most detrimental effect on FL learning of all affective factors.  As there are no studies about FLTA in the Republic of Serbia, this paper aims to identify the level of FLTA experienced by Serbian in-service teachers, to find out whether they are familiar with the phenomenon, whether the familiarity with FLTA can help to alleviate it, and whether good methodological instruction and practical training can help future teachers overcome the problem. Mixed methods research was performed using the questionnaire designed for its purpose, which elicited both quantitative and qualitative data. A total of 585 in-service FL teachers participated. The results show that the respondents experience FLTA to a moderate degree. However, the majority of the respondents are not aware that FLTA is studied as a specific and common phenomenon in international literature. According to the obtained results, FLTA can be reduced by raising FL teachers’ awareness of it, and the faculties of philology can contribute to this by providing future teachers with high-quality methodological and practical training. If they overcome FLTA, FL teachers will be able to create a relaxed atmosphere in the classroom, boost learners’ self-confidence, and reduce FLLA. Consequently, the target language usage and learner engagement, as well as teaching efficiency, would be maximised.
Keywords: foreign language teaching; foreign language learning; foreign language anxiety; foreign language teaching anxiety; foreign language learning anxiety